2009
DOI: 10.1093/qjmed/hcp064
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality of falls amongst older people in primary care in the United Kingdom

Abstract: These data suggest that more than 475,000 fall events in older people are recorded in general practice each year in the UK, and are associated with increased mortality and relative deprivation. The underlying incidence rate has remained stable in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 9 publications
0
25
1
4
Order By: Relevance
“…In our study, 64% of the post-polio patients reported at least one fall in the last 6 months. The prevalence of falls in our cohort is very striking when compared to the falls risk in a general population aged ≥65 years [26,27]. Gribbin et al [26] showed that 33% of the adults aged ≥65 years reported one or more falls per year.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our study, 64% of the post-polio patients reported at least one fall in the last 6 months. The prevalence of falls in our cohort is very striking when compared to the falls risk in a general population aged ≥65 years [26,27]. Gribbin et al [26] showed that 33% of the adults aged ≥65 years reported one or more falls per year.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of falls in our cohort is very striking when compared to the falls risk in a general population aged ≥65 years [26,27]. Gribbin et al [26] showed that 33% of the adults aged ≥65 years reported one or more falls per year. In a similar study by Boyd and Stevens [27], 9.6% of the adults aged ≥65 years reported one or more falls in a 3-month period, but only 10% of these falls resulted in a serious injury or a fracture requiring hospitalization [27].…”
Section: Discussionmentioning
confidence: 84%
“…4 In the UK the incidence ratio of falls is 3.58/100 individuals per year, which gives 475,000 annual falls. 5 Falls are relevant because a high percentage of them have consequences for health. Between 41% 1 and 73.9% 2 of falls have physical/functional consequences (superficial wounds, fractures, mobility limitations) and/or psychosocial consequences (fear of falling, the perception that falling changed one's life).…”
Section: Introductionmentioning
confidence: 99%
“…According to research carried out in the UK on individuals of 60 or more years who lived in community, mortality for recurrent fallers was about twice that of general population controls. 5 It is likely that the consequences of falls on the health of the community-dwelling elderly will affect their perception of their health-related quality of life (HRQL). Nowadays, we rely on quite robust questionnaires, that can be administered in a quick and simple way, and that allow us to obtain valid and reliable results, to evaluate HRQL as EuroQol-5D (EQ-5D).…”
Section: Introductionmentioning
confidence: 99%
“…Between 22 and 40% of all community-dwelling people aged 65 years or older fall at least once a year (1)(2)(3). With an aging population, the absolute number of people who sustain a fall and concomitant injury will increase.…”
Section: Introductionmentioning
confidence: 99%